2012
DOI: 10.1183/09031936.00092212
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of hyperoxia-induced lung injury using a sphingolipid-based intervention

Abstract: The aim of this study was to characterise lung function and bronchoalveolar lavage sphingolipid profile in newborn mice during hyperoxia exposure and recovery in room air, and to examine the effect of D-sphingosine supplementation during recovery.Newborn mice were exposed to 80% oxygen for 4 weeks and allowed to recover in room air for another 4 weeks. Lung function measurements and morphometrical analysis of lung tissue were performed and bronchoalveolar lavage fluid was collected during hyperoxia and recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 34 publications
4
40
1
Order By: Relevance
“…Afterwards the Flexivent rodent ventilator (Scireq, Montreal, Canada) was used to invasively assess lung function (described in detail in the online supplement) following a protocol previously published (33). …”
Section: Methodsmentioning
confidence: 99%
“…Afterwards the Flexivent rodent ventilator (Scireq, Montreal, Canada) was used to invasively assess lung function (described in detail in the online supplement) following a protocol previously published (33). …”
Section: Methodsmentioning
confidence: 99%
“…These data suggest that prolonged exposure to hyperoxia produces a physiological and histological picture similar to BPD, which may be mediated in part by inflammatory cytokines. Other groups have used similar models based on 28 days of hyperoxia exposure (81,90). However, the success of the 28-day hyperoxia model is limited in its ability to mimic new BPD, which is not characterized by as significant an increase in pulmonary fibrosis as the old definition of BPD (11).…”
Section: Rodent Models Of Pulmonary Diseasementioning
confidence: 99%
“…We found that S1P analog D-sphingosine promoted recovery of ceramide levels and histology but not lung function after hyperoxiainduced alveolar arrest in a mouse model of BPD. 32 As described earlier, S1P analogs also protect mice from radiation-induced lung injury 33 and has been shown to improve alveolar cell survival and decrease alveolar airspace enlargement in a VEGF receptor inhibitor-induced model of pulmonary emphysema. 98 Inhibiting serine palmitoyltransferase with myriocin decreased lung infl ammation and fi brosis, as measured by collagen and a -smooth muscle actin expression, after thoracic radiation with 20 Gy and delayed the onset of radiation-induced death from 15 to 18 weeks.…”
Section: Interventions In the Sphingolipid Pathwaymentioning
confidence: 91%
“…As we have recently demonstrated, altered sphingolipid levels play a role in hyperoxia-induced lung injury or BPD. 32 We reported a rise in ceramide levels during hyperoxia exposure in newborn mice, correlating with decreased lung function, which returns to control levels during recovery in normoxia. By adding an S1P analog, D-sphingosine, during the recovery period, ceramide levels decrease more rapidly, and histologic abnormalities are ameliorated.…”
Section: Sphingolipids and Bpdmentioning
confidence: 96%